Geoffrey Ronald Burbidge. 24 September 1925 — 26 January 2010. (31st December 2017) - Longair, Malcolm; Rees, Martin
Abstract : Geoffrey (Geoff) Burbidge's career spanned the tumultuous years when astronomy was transformed from a purely optical science to a multi-wavelength discipline through the development of new types of astronomy—radio, X-ray, γ -ray, cosmic ray physics. These offered new astrophysical and cosmological challenges, which he grasped with relish. To all of these disciplines, Geoff, often in collaboration with his wife Margaret Burbidge (FRS 1964), made pioneering contributions, particularly in the areas of the synthesis of the chemical elements, the physics of extragalactic radio sources, the rotation curves of galaxies, the dark matter problem in clusters of galaxies, the physics of accretion discs and the origin of cosmic rays. He also espoused less popular causes such as the non-cosmological nature of the redshifts of quasars and was sceptical about the standard Big Bang picture of the origin of the large-scale structure and dynamics of the Universe. He was a flamboyant and outspoken astrophysicist who challenged his colleagues about their deeply held views on all aspects of astrophysics and cosmology. His service to the community included five years as director of the US Kitt Peak National Observatory, based in Tucson, Arizona, and as a most effective editor of Annual Review of Astronomy and Astrophysics for over 30 years and the Astrophysical Journal.